2014
DOI: 10.1177/0040517513512400
|View full text |Cite
|
Sign up to set email alerts
|

Effect of domestic laundering on the fragment protective performance of fabrics used in personal protection

Abstract: UK Armed Forces wear items of clothing that incorporate fragment protective fabrics (Tier 1 Pelvic Protection) and other items of clothing are under development (e.g. Improved Under Body Armor Combat Shirt). The long-term robustness of such garments is of interest. In this paper four candidate fabrics (knitted silk, ultra-high molecular weight polyethylene felt, para-aramid felt and a woven para-aramid) were investigated. The effect of laundering on 0.24 g chisel-nosed fragment simulating projectile ballistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…According to standard procedures, the Probit analysis model was used, using a 95% confidence interval (results of the regression analysis are shown in Figure 11). 25…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to standard procedures, the Probit analysis model was used, using a 95% confidence interval (results of the regression analysis are shown in Figure 11). 25…”
Section: Resultsmentioning
confidence: 99%
“…The results of 20 shots were taken per group of specimens, which provided reliable statistical analysis. Results were statistically analyzed using the Probit method as outlined by Helliker 25 to compare the two groups. The results were plotted as a function of projectile penetration probability against projectile impact velocity, and the gradients and the V 50 velocities (the impact velocity at which there is a 50% likelihood of sample complete penetration) of the regression graphs were compared.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental factors such as temperature, humidity, impurity, and dampness, to name but a few that would vary depending on the location of the field, would all contribute to the performance of the protective fabrics. Immersion in water ( Bazhenov, 1997 ; Li et al, 2016 ) and domestic laundering ( Helliker et al, 2014 ) have been shown to reduce the performance of some ballistic protective fabrics. The effect of these factors on the protective ability of protective fabrics should be determined experimentally, and the proposed apparatus and methodology presented here offers a reproducible test bed to do so.…”
Section: Discussionmentioning
confidence: 99%
“…Although the body armour is dried between patrols, the effect of regular soakings with salt water and drying has also not been previously studied. Laundering (washing and drying cycles) can affect the ballistic protective performance of fabrics (Helliker et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%